Faraday waves and droplets in quasi-one-dimensional Bose gas mixtures - Abdullaev, F Kh [UNESP]; Gammal, A.; Kumar, R. K.; Tomio, Lauro [UNESP] (IOP Publishing, 2019)
Faraday waves in mixtures of Bose gases are studied by taking into account quantum fluctuations beyond the Gross-Pitaevskii mean-field formalism with the Lee-Huang-Yang term. For that, a Bose-Einstein condensed binary atomic mixture is assumed trapped in cigar-type geometry, having the inter- A nd intra-species scattering lengths periodically varying in time. The period of the Faraday patterns is shown to be quite sensitive to the estimated value obtained by the beyond mean-field contribution, which can be used to measure quantum fluctuations in the ground state of the quasi-one-dimensional mixture. By studying the influence of the above nonlinear periodic modulations on quantum droplet dynamics, we also show that nonlinear resonances are excited in the oscillation widths of the quantum droplets. Variational predictions confirm numerical simulations for the corresponding formalism.
Keywords: Bose-Einstein condensates; dynamics properties of condensates; Faraday waves; quantum droplets